Modified Prone Position pada Pasien Long COVID-19 untuk Meningkatkan Saturasi Oksigen Perifer - Chairul Huda; Agung Waluyo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to measure the effect of the Modified Prone Position on Ny.A patients with long Covid-19 conducted at P Hospital in Jakarta. The research method used is a case study. The results of this study indicate that the appropriate administration of the modified prone position can increase oxygen saturation. In conclusion, Modified prone position is effective in increasing oxygen saturation, reducing short-term oxygen demand and improving patient sleep quality. Keywords: Breathing Exercise, Long COVID-19, Prone Position